Hungarian Monitoring, 20 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Nationalist beatings in Tashkent on festival of People's Friendship - Thatcher in Tokyo Domestic Affairs: - Three-sided economic conciliation talks - Zoltán Király's proposal that parliament discusses Hungarian Socialist Workers' Party (MSZMP) property - Szűrös's Washington press conference - On the future of the Hungarian Socialist Workers' Party (MSZMP) - Hungarian-Czechoslovak international legal experts continue discussions of Gabčíkovo-Nagymaros dam Economy: - Mid-range concept for the agricultural sector - International economists' conference - Rába Machine Works rejects opposition's interfering in economic decisions Külpolitika: - Nacionalista verekedés Taskentben a Népek Barátsága fesztiválon - Thatcher Tokióban Belpolitika: - Háromoldalú gazdasági egyeztető tárgyalások - Király Zoltán indítványozta, hogy a parlament tárgyaljon az MSZMP vagyonáról - Szűrös washingtoni sajtóértekezlete - Az MSZMP jövőjéről - Bős-Nagymarosról folytatott magyar - Csehszlovák nemzetközi jogi szakértői tárgyalások Gazdaság: - Az agrárágazat középtávú koncepciójáról - Nemzetközi közgazdász konferencia - A Rába Gépgyár visszautasítja az ellenzék beleszólását gazdasági döntésekbe